2013
DOI: 10.1155/2013/657259
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvant Magnetic Fields in Radiotherapy on Non-Small-Cell Lung Cancer CellsIn Vitro

Abstract: Objectives. To explore sensitization and possible mechanisms of adjuvant magnetic fields (MFs) in radiotherapy (RT) of non-small-cell lung cancer. Methods. Human A549 lung adenocarcinoma cells were treated with MF, RT, and combined MF-RT. Colony-forming efficiency was calculated, cell cycle and apoptosis were measured, and changes in cell cycle- and apoptosis-related gene expression were measured by microarray. Results. A 0.5 T, 8 Hz stationary MF showed a duration-dependent inhibitory effect lasting for 1–4 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…NSCLC are often diagnosed at late stages [ 8 ]. For patients with advanced stages of NSCLC when surgical excision is not an option, the adjuvant chemotherapy and radiotherapy has been extensively used [ 9 ]. However, unlike small-cell lung cancer (SCLC) that often has neuroendocrine (NE) features, NSCLC is usually chemoresistant.…”
Section: Introductionmentioning
confidence: 99%
“…NSCLC are often diagnosed at late stages [ 8 ]. For patients with advanced stages of NSCLC when surgical excision is not an option, the adjuvant chemotherapy and radiotherapy has been extensively used [ 9 ]. However, unlike small-cell lung cancer (SCLC) that often has neuroendocrine (NE) features, NSCLC is usually chemoresistant.…”
Section: Introductionmentioning
confidence: 99%
“…62 In the last 5 years, three studies have been published on the topic of combined SMF and ionising radiation exposure in human cancer in vitro models. [63][64][65] Viability of lung adrenocarcinoma cells (cell line A549) treated with 0.5 T SMF alone for 1 to 4 h was significantly inhibited by approximately 10% relative to untreated cells (p < 0.05). 63 Gene chip analysis revealed that SMF exposure of 1 h produced alterations in gene expression associated with the promotion of cell cycle arrest and apoptosis.…”
Section: Biological Effects Of Combined Ionising Radiation and Strongmentioning
confidence: 98%
“…[63][64][65] Viability of lung adrenocarcinoma cells (cell line A549) treated with 0.5 T SMF alone for 1 to 4 h was significantly inhibited by approximately 10% relative to untreated cells (p < 0.05). 63 Gene chip analysis revealed that SMF exposure of 1 h produced alterations in gene expression associated with the promotion of cell cycle arrest and apoptosis. A549 clonogenic survival following X-ray irradiation was significantly impaired in cells exposed to SMF (p < 0.05), e.g.…”
Section: Biological Effects Of Combined Ionising Radiation and Strongmentioning
confidence: 98%
See 2 more Smart Citations